Investigating Foodborne Cryptosporidium and Giardia in Clams Harvested Near Iqaluit, Nunavut - Manore, Anna Jane Wilson (University of Guelph, 2018)
High prevalences of Cryptosporidium and Giardia were reported in enteric illness patients in Nunavut, Canada, with a foodborne, waterborne, or animal source of parasites suspected. Clams (Mya truncata) are a commonly consumed, culturally important, and nutritious country food in Iqaluit, Nunavut; however, shellfish may concentrate pathogens from surrounding waters. EcoHealth approaches were used to investigate locally-harvested clams as a potential source of Cryptosporidium and Giardia for Iqaluit residents. Following molecular method validation, clam hemolymph (n=328) and digestive gland (n=390) samples were screened for Cryptosporidium and Giardia via PCR followed by sequence analyses. Giardia was confirmed in hemolymph from 2 clams, while Cryptosporidium was not detected. The Giardia sequences were identified as zoonotic Giardia enterica assemblage B, and may have originated from human or animal sources. Study results are intended to inform public health practice and planning. ArcticNet Ontario Graduate Scholarship University of Guelph Canadian Institutes of Health Research Northern Scientific Training Program